2005
DOI: 10.1063/1.1851434
|View full text |Cite
|
Sign up to set email alerts
|

Spin-current-induced magnetization reversal in magnetic nanowires with constrictions

Abstract: We have performed experiments on current-induced domain-wall motion ͑CIDWM͒ in the case of the domain walls ͑DW͒ trapped within the nanoscale constrictions in patterned NiFe structures. Direct observation of current-induced magnetization reversal was achieved and critical current densities j c were measured in the presence of easy-axis magnetic fields. The direction of CIDWM was found to be along the direction of the electron motion in absence of an applied magnetic field and in the direction of the field when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
6

Year Published

2006
2006
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
1
12
0
6
Order By: Relevance
“…We have observed this wall structure using magnetic force microscopy (MFM) imaging in permalloy nanowires more than 20 nm thick. Florez, Krafft and Gomez (2005) have reported similar structures in permalloy wires, 40 nm thick.…”
Section: Head-to-head Domain Walls In Soft Magnetic Nanowiresmentioning
confidence: 49%
See 2 more Smart Citations
“…We have observed this wall structure using magnetic force microscopy (MFM) imaging in permalloy nanowires more than 20 nm thick. Florez, Krafft and Gomez (2005) have reported similar structures in permalloy wires, 40 nm thick.…”
Section: Head-to-head Domain Walls In Soft Magnetic Nanowiresmentioning
confidence: 49%
“…In most of these experiments, the DW is first pinned at either a defect (Thomas et al, 2006;Laufenberg et al, 2006b;Grollier et al, 2004;Lim et al, 2004), or a notch (Florez, Krafft and Gomez, 2005;Hayashi et al, 2006b;Klaui et al, 2005c) or at a cross (Ravelosona et al, 2005). In one report , a quite different experimental method was used: the propagation field along a nanowire is measured while dc currents of both polarities are applied.…”
Section: Field Dependence Of the Critical Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a), together with the magnetization distributions along the x-direction. The exact position of the wall is fixed by a notch which pins the domain wall [10,11]. If the wire is not intentionally notched then the position of the wall, an always-present surface 'bump' pins wall in a real structure.…”
Section: Resultsmentioning
confidence: 99%
“…The results are investigated using the anisotropic magnetoresistance (AMR) effect and micromagnetic simulation. Recently, the studies indicated that the presence of even weak magnetic fields can dramatically boost the speed of the domain wall motion [13]. Here, we report current induced domain wall study in a single layer ferromagnetic horseshoe structure.…”
Section: Introductionmentioning
confidence: 91%